Nutrient Cycling in Agroforestry Systems of the Semi-arid Tropics of Africa - Rao, M R; Mafongoya, P L; Kwesiga, F R; Maghembe, J A (Annals of Arid Zone, 2016)
Trees integrated with crops in time and/or space mediate nutrient cycling on farms by increasing the supply and availability of nutrients in the crop root zone and reducing nutrient losses. However, quantitative information is lacking on biological nitrogen fixation and nutrients recycled in semi-arid agroforestry due to the control of losses by trees, and most information available is on nutrients recycled through their above- and below-ground biomass. The potential for exploiting nutrient cycling in simultaneous agroforestry systems is constrained by a low and erratic water supply in the semi-arid areas of Africa. In parkland systems, there is a limited scope for increasing nutrient cycling because of the small quantity of biomass added into soil from low tree density in the system. However, trees in these traditional systems are more important for economic products in terms of poles, timber, fruits, etc., and have ecological benefits such as the reduction of nutrient and water losses. Although hedgerow intercropping uses high tree density and increases the nitrogen (N) supply in the soil, crops nevertheless fail to benefit due to competitior1\between trees and crops for water. Contour hedgerows can conserve nutrients by arresting soil erosion on moderately sloping lands and are worthy of consideration for both soil conservation and fodder production. Mixed intercropping of Gliricidia sepium and maize with efficient tree management appears to be promising in some areas and needs further testing before widespread dissemination. Sequential systems with short-duration leguminous trees and shrubs, exemplified by 2-year Sesbania sesban rotated with crops, and biomass transfer systems are both efficient in nutrient cycling and increasing crop yields. Therefore, these systems can be considered for dissemination depending on the socio-economic conditions. The potential for using biomass transfer \ systems is constrained by the availability of biomass outside the farms, land for its production on farms and labor for its application. Although these agroforestry systems provide an adequate quantity of N for moderate cereal yields, they cannot meet the phosphorus (P) requirements of crops in P-deficient soils, which should be supplemented through inorganic P sources. Nutrient cycling using livestock is less efficient due to N losses by volatilization and leaching than direct use of biomass as green manure. The use of palatable and high quality biomass as fodder is three to five times more economical than green manure. While agroforestry clearly has a definite role to increase nutrient cycling in low input systems, no single technology can guarantee controlling nutrient depletion in the long term. The choice of different technologies to suit different niches of the farm and their integration with inorganic nutrients is important for sustainable production even on smallholders' farms in the semi-arid Africa.